2000
DOI: 10.1046/j.1365-2265.2000.01120.x
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal responsiveness to high, low and very low ACTH 1–24 doses in obesity

Abstract: This study shows that the cortisol, aldosterone and dehydroepiondrosterone responses to high, low and very low ACTH doses in obese women overlap with those in age-matched lean controls; these findings suggest normal sensitivity of the different zones of the adrenal cortex to ACTH in obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 44 publications
2
11
2
Order By: Relevance
“…They were also unable to demonstrate an effect of intermittent, light exercise on cortisol responses but did find an independent effect of central obesity on the 30‐min cortisol response in men. However, as others have shown no effect of obesity on cortisol responses to ACTH, it is unclear whether waist circumference‐specific reference limits are needed. Dhillo et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were also unable to demonstrate an effect of intermittent, light exercise on cortisol responses but did find an independent effect of central obesity on the 30‐min cortisol response in men. However, as others have shown no effect of obesity on cortisol responses to ACTH, it is unclear whether waist circumference‐specific reference limits are needed. Dhillo et al .…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four of the premenopausal female participants were taking an oestrogencontaining oral contraceptive pill (OCP), containing between 20 and 35 lg of ethinyloestradiol, at the time of testing. Mean age (and range) was 37Á1 (22-62), 40Á7 (20-66) and 28Á7 (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) years in male, non-OCP female and OCP female groups, respectively. The study protocol was approved by the South East Wales Research Ethics Committee, Cardiff University (study sponsors) and the UK Competent Authority (the Medicines and Healthcare Products Regulatory Authority).…”
Section: Subjectsmentioning
confidence: 99%
“…A precedent for altered adrenal responsiveness to ACTH with level of adiposity has been provided in humans although the results are conflicting. Adrenal responsiveness to ACTH was reported to be higher in women [7, 29] and men [12] with visceral adiposity while another study found no differences in cortisol, aldosterone and dehydroepiandrosterone responses to ACTH between obese and lean women [59]. In our study, the lean ewes had only a transient increase in ACTH during isolation/restraint but a more robust increase in cortisol during isolation/restraint stress whereas the fat ewes had clear increases in both ACTH and cortisol.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined the responses of plasma aldosterone concentrations to the low‐dose ACTH 1–24 test 12,22,23 despite the expectation of finding different responses in dexamethasone suppressible aldosteronism and tumours 23 . In order to explore the use of the low‐dose Synacthen test to assess aldosterone secretion we have critically examined the plasma aldosterone response to low doses of Synacthen to determine the optimum blood sampling interval in normal subjects prior to assessing value in clinical conditions in which the function is altered by disease.…”
Section: Introductionmentioning
confidence: 99%